2014
DOI: 10.4236/ojog.2014.415136
|View full text |Cite
|
Sign up to set email alerts
|

Can Vaginal Washing Fluid Urea, Creatinine and Qualitative <i>β</i>-hCG Diagnose Suspected Premature Rupture of Membranes?

Abstract: Several markers have been studied to diagnose PROM but there is still limitation with a gold standard test for the diagnosis [1]. Objective: To evaluate and compare the accuracy of urea, creatinine and hCG in vaginal fluid washing for diagnosis of PROM and to determine cut off levels. Type of the study: Prospective study performed on pregnant women in their third trimester who are coming to Kasr El Ainy maternity outpatient clinic with history of fluid leakage. Patients and methods: 150 patients between 26 -40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
1
14
1
Order By: Relevance
“…16 Researchers had who used a cut-off point 25 mUI/mL also achieved sensibility and specificity rates higher than than 90%, which suggest this can be an appropriate value. 1,12,17,18 During pregnancy, the cervical glands release hCG in the vaginal fluid, but the concentration remains lower than 10 mUI/mL after the 20th gestational week, 1 which supports the possibility of performing the β-hCG qualitative test with a cut-off point of 10 mUI/mL. However, in this study, the β-hCG-10 test provided a low accuracy (58.6%).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…16 Researchers had who used a cut-off point 25 mUI/mL also achieved sensibility and specificity rates higher than than 90%, which suggest this can be an appropriate value. 1,12,17,18 During pregnancy, the cervical glands release hCG in the vaginal fluid, but the concentration remains lower than 10 mUI/mL after the 20th gestational week, 1 which supports the possibility of performing the β-hCG qualitative test with a cut-off point of 10 mUI/mL. However, in this study, the β-hCG-10 test provided a low accuracy (58.6%).…”
Section: Discussionmentioning
confidence: 53%
“…Its prevalence ranges from [8][9][10][11][12][13][14][15][16][17][18][19].53% of term pregnancies, and from 2-25% of all pregnancies. Traditionally, the diagnosis of PROM involves vaginal discharge history of amniotic fluid verified at speculum examination with the ferning test in the microscopic exam and the nitrazine test of the vaginal discharge.…”
Section: Introductionmentioning
confidence: 99%
“…In a study performed by Mangano et al 2000, it was performed on 52 women (20 women with intact membranes, 21 women with definitive ROM and 11 women with suspicious ROM), the researchers concluded that vaginal washing fluid B-HCG is a suitable, cheap and non-invasive method for the diagnosis of PPROM [25] [26]. In the other hand another study performed by Shahin and Raslan 2006 which evaluated vaginal fluid concentrations of three markers (AFP, prolactin and B-HCG), they were significantly higher in the PROM group than in the control group (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Urea and creatinine have shown promise in multiple studies for highly sensitive and specific detection of PROM with close to 100% sensitivity and 100% specificity, although the optimal cutoff values have varied between studies. 203,216,217,223229 In these studies, the urea and creatinine are measured from vaginal washes, where 3 to 5 mL of saline is injected into the posterior vaginal fornix and subsequently aspirated with the same syringe. 226 Urea is detected with a spectrometer and creatinine with an enzymatic based assay, but a ladder-based LFA for creatinine was developed in the laboratory which runs within 20 minutes and has 90% agreement with the traditional Jaffe method.…”
Section: Diagnostics For Maternal Healthmentioning
confidence: 99%